PENGETAHUAN IBU HAMIL TENTANG PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) DI PUSKESMAS MADUKARA 2 KECAMATAN MADUKARA KABUPATEN BANJARNEGARA TAHUN 2008 - Ariya Dwi Kristiyanti; Feti Kumala Dewi (Universitas Harapan Bangsa Purwokerto, 2008)
Background: Maternal mortality rates according to Indonesian health demographic survey in2007 was as high as 282 / 100,000 live births, P4K is the latest program created to help thegovernment nenurunkan Maternal Mortality. In Banjarnegara district maternal mortality is 122/ 100,000 live births, in Puskesmas Madukara 2 maternal mortality rate of 12.5 / 100,000 livebirths. From a review of pre survey 33% of pregnant women lack knowledge about P4K well.Objective: To determine the knowledge overview about P4K pregnant women at health centersMadukara 2 based on age, education, employment, resources, socio-economics.Methods: This research method is descriptive based on primary data by cross sectionalapproach taken by the questionnaire to 53 pregnant women trimester I, II, and III in the roomKIA with sampling techniques accidental sample at the health center Madukara 2 SubdistrictMadukara Banjarnegara district on June 21 until July 1, 2008.Results: Overview knowledge of pregnant women about P4K by the largest age 20-35 years old(58.3%) with a fairly good knowledge, based on the largest education PT / Diploma / SI / SII(100%) with good knowledge, based on the largest job does not work (63.6%) with a fairly goodknowledge, based on the largest print media resources (100%) with a fairly good knowledge,based on the socio-largest economy equal to Rp. 622 000 (66.7%) with fairly good knowledge.Conclusion: Overview knowledge of pregnant women according to age, education, employment,resources, socio-largest economy with fairly good knowledge.Keywords: Knowledge, pregnant women, Program Planning and Delivery ComplicationsPrevention (P4K).